Role of eccentric cycling in older adults affected by sarcopenia and heart failure: a feasibility and efficacy study protocol - Federico Schena; Giovanni Benfari; Cantor Tarperi; Roberto Di Marco; Valentina Cavedon; Valentina Muollo; Samuel D’Emanuele; Mahsa Amini; Shelley Keating; Matteo Lanceni; Martina Setti; Laura Ghiotto (BMJ Open Sport & Exercise Medicine)
Physical inactivity is a major risk factor for both cardiovascular diseases and sarcopenia, with exercise playing a crucial role in managing these conditions. While resistance training is widely recommended for sarcopenia, alternative exercise modalities like eccentric cycling (EC) remain largely underexplored, particularly for patients with heart failure (HF) and sarcopenia. EC, which involves muscle lengthening during contraction, offers advantages such as lower metabolic and circulatory demands than conventional concentric cycling, making it an attractive option for frail individuals with limited physical capacity. EC has emerged as a promising method, providing mechanical overload at lower energy expenditure.Despite its potential, studies on EC in older adults with HF and sarcopenia are scarce. Therefore, this study aims to evaluate the feasibility of a 12-week EC programme in this population. Before training, participants will undergo a 2-week familiarisation period with a gradually increasing workload to ensure adaptation and minimise discomfort. The training programme will start with two sessions per week, progressing to three sessions per week, with workloads adjusted every 2 weeks to maintain the target rate of perceived exertion. The study will also assess the impact of EC on body composition, muscle strength and neuromuscular activity of upper and lower limbs, cardiorespiratory fitness and physical performance. Despite potential challenges such as patient adherence and small sample size, the study’s findings are expected to provide important first data regarding the feasibility and benefits of EC for improving functional capacity in this high-risk population.